IMPLEMENTATION OF PBL METHOD IN IMPROVING STUDENTS' LEARNING INTEREST IN AQIDAH AKHLAK SUBJECT AT MTsN 1 BONE - muh syahrul sarea; , Misbah Ahmad; Muh. Taufik Al Fauzy; Andi Febyarni Reski Angkara; Elly Yanti Nur (Acceleration: Multidisciplinary Research Journal, 2023)
This study is a type of Classroom Action Research that aims to obtain information about efforts and attempts to improve students' interest in learning in the eighth grade of MTsN 1 Bone, using the Problem-Based Learning (PBL) method. The research was conducted cooperatively or collaboratively in two cycles. The study was conducted at MTsN 1 Bone with a population of 32 students and a saturated sample of 32 students. The data collection techniques used in this study were interviews with a predetermined educator and direct observations of the researched class, which was class VIII C. The data analysis technique used was Descriptive Analysis. The results of the study showed that the use of the Problem-Based Learning method was able to increase students' interest in learning. Students' interest in learning consisted of Interest, Attention, Enjoyment, and Discipline. In the first cycle, students' interest in learning obtained a final score of 55%, indicating low interest. In the second cycle, the final score of students' interest in learning reached 84%, indicating good interest.